Respostas

2013-09-30T10:53:16-03:00
{-x + 9 y = -12      (x1)
{ 3x +y = -20

fica assim:
-3x + 9y = -12
3x  + y = -20
       10y = - 32
y = - 32/10 = -12
3x + ( -12) = -20
  3x- 12 = -20
3x = -20 +12
x = - 8

{ 4x + 3y = 6    x(-1)
{ 4x +y = 2
   
fica assim: { -4x - 3y = -6
                 { 4x  +y  = 2
                         -2y = - 4    (x-1)
                           y= 4/2 = 2

4x + y = 2
4x + 2 = 2
4x= 2 - 2
4x =0
x= 4

{ x + y = 33
{ 2x - y = -3
  3x       = 30
x= 30/3 = 10

10 + y = -3
 y= -3 - 10
 y = -13